Antibacterial effects of gold nanoparticles functionalized with the extracted peptide from Vespa orientalis wasp venom. (25th October 2018) - Jalaei, Jafar; Layeghi‐Ghalehsoukhteh, Somayeh; Hosseini, Arsalan; Fazeli, Mehdi
Abstract : The development of novel antimicrobial strategies is necessary because of the escalation of multidrug‐resistant pathogens. Recently, antimicrobial peptides and their combination with nanoparticles were regarded as a promising tool to target drug‐resistant pathogens. Herein, we evaluated antimicrobial efficacy of a peptide extracted from Vespa orientalis wasp venom and also its conjugation with gold nanoparticles. Nanoparticle conjugation measurement was done by evaluating the absorbance changes of the surface plasmon resonance band of gold nanoparticles at 555 nm. A significant increase in the antibacterial activity against gram negative and positive bacteria was obtained when the extracted peptide conjugated with gold nanoparticles. Finally, the results show that this new peptide‐AuNps has the high practical potential for antibacterial activity and may provide an alternative therapy for bacterial infection. Abstract : The extracted peptide from vespa orientalis wasp venom showed antibacterial effects. In order to increase this activity, we conjugated this peptide with gold nanoparticles. the resulted conjugation revealed notably increased bactericidal activity invitro.